2019
DOI: 10.1016/j.jval.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Health Services Researchers

Abstract: Background: Machine learning is increasingly used to predict healthcare outcomes, including cost, utilization, and quality.Objective: We provide a high-level overview of machine learning for healthcare outcomes researchers and decision makers.Methods: We introduce key concepts for understanding the application of machine learning methods to healthcare outcomes research. We first describe current standards to rigorously learn an estimator, which is an algorithm developed through machine learning to predict a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
123
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(134 citation statements)
references
References 30 publications
(27 reference statements)
0
123
0
3
Order By: Relevance
“…Machine learning methods can learn complex structures by incorporating numerous variables with high dimensional data [9]. Excellent performance of these methods has been validated in health service [10] and health outcomes studies [11]. Regularized logistic regression (RLR), as the fundamental and most commonly used machine learning method, is a generalized linear regression model for probability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning methods can learn complex structures by incorporating numerous variables with high dimensional data [9]. Excellent performance of these methods has been validated in health service [10] and health outcomes studies [11]. Regularized logistic regression (RLR), as the fundamental and most commonly used machine learning method, is a generalized linear regression model for probability analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from. 12 Tutorial: Machine Learning for Precision Medicine -Basu et al come using variables with few classes, rather than with multi-class or continuous variables, can often be modeled best through boosting. 8,9 Our statistical code illustrates both approaches, which are discussed further below.…”
Section: Bagging and Boostingmentioning
confidence: 99%
“…The ML random forest approach, fully described in the Supplementary Material, was applied to build predictive models [20]. The random forest algorithm [21] is a stochastic ensemble method that uses bagging, a combination of bootstrapping and aggregation of weak learners, more specifically, decision trees, seeking to detect patterns in data and use these to predict outcomes, in our case, NPS [19].…”
Section: Machine Learningmentioning
confidence: 99%
“…An example of this would be the calculation of the prevalence of NPS in population samples. While this design has been previously applied in cardiovascular research [17] and Alzheimer's disease neuroimaging [18], no examples have been reported of its use to measure features of dementia-related NPS at population level [19]. Therefore, the objective of this study was to construct and validate predictive models based on ML tools to identify the presence of psychotic and/or depressive symptoms in dementia-diagnosed patients from administrative and clinical databases that cover entire populations.…”
Section: Introductionmentioning
confidence: 99%